2013
DOI: 10.1007/s11113-013-9297-2
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking in Same-Sex and Different-Sex Unions: The Role of Socioeconomic and Psychological Factors

Abstract: Cigarette smoking has long been a target of public health intervention because it substantially contributes to morbidity and mortality. Individuals in different-sex marriages have lower smoking risk (i.e., prevalence and frequency) than different-sex cohabiters. However, little is known about the smoking risk of individuals in same-sex cohabiting unions. We compare the smoking risk of individuals in different-sex marriages, same-sex cohabiting unions, and different-sex cohabiting unions using pooled cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 130 publications
(187 reference statements)
0
12
0
Order By: Relevance
“…The NHIS has been used in prior research to examine health disparities for younger adults in co-residential same-sex relationships (Heck, Sell, & Gorin, 2006; Cochran & Mays, 2012; Liu, Reczek & Brown, 2013; Reczek, Liu & Brown, 2013) and has not been utilized to examine differences in health or disability status among older adults. Consistent with studies on older LGB adults (Fredricksen-Goldsen, et al, 2011; 2013a; 2013b; Wallace et al ., 2011), we restrict our sample to older, cohabiting, partnered adults 50 years and older in the NHIS.…”
Section: Methodsmentioning
confidence: 99%
“…The NHIS has been used in prior research to examine health disparities for younger adults in co-residential same-sex relationships (Heck, Sell, & Gorin, 2006; Cochran & Mays, 2012; Liu, Reczek & Brown, 2013; Reczek, Liu & Brown, 2013) and has not been utilized to examine differences in health or disability status among older adults. Consistent with studies on older LGB adults (Fredricksen-Goldsen, et al, 2011; 2013a; 2013b; Wallace et al ., 2011), we restrict our sample to older, cohabiting, partnered adults 50 years and older in the NHIS.…”
Section: Methodsmentioning
confidence: 99%
“…According to fundamental cause theory, the health disparities of gay and lesbian individuals are due, in part, to social stigma and historically unequal access to legal and institutional benefits of marriage that contribute to socioeconomic disadvantage; socioeconomic disadvantage is in turn associated with increased stress, psychological distress, and worse self-rated health (Hatzenbuelher, McLaughlin, Keyes, & Hasin, 2010; Meyer, 2003a,b). Several studies show that SES also appears to play a role in differences between same-sex cohabiting couples and their different-sex married and cohabiting counterparts on both self-rated health and health behavior (Denney et al, 2013; Liu et al, 2013; Reczek, Liu, & Brown, 2014; Reczek, Liu, & Spiker, 2014). For example, Liu and colleagues found that the same-sex cohabiting were disadvantaged in health relative to the different-sex married, but that the same-sex cohabiting’s higher SES actually protected them from even worse relative self-rated health.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…These patterns appear to extend to same-sex cohabitors, wherein single groups have better health than same-sex cohabiting groups as a result of selection and resources. In addition, higher rates of substance use among same-sex cohabiting women across all racial-ethnic groups than their unpartnered single counterparts may reflect the overall higher rates of substance use among those in the lesbian community (Reczek et al 2014; Rothblum and Solovay 2009); relative to single women, who appear healthier, all racial-ethnic same-sex cohabiting groups may experience a disadvantage. Same-sex cohabiting women’s greater substance use may also be exacerbated by being in a same-sex cohabitating relationship as a result of convergence processes (Reczek et al 2014), wherein partners of the same sex promote unhealthy behavior in one another.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it may be that cohabitors in this sample define themselves as married as a symbolic act (Reczek et al 2009), or were legally married in a state that allows same-sex marriage (e.g., Massachusetts), but lived in another state and receive no institutional benefits from this marriage (Rosenfeld 2007). This implies a possible conflation of the same-sex married and cohabiting; thus, we follow previous studies (e.g., Denney et al 2013; Liu et al 2013; Reczek et al 2014) to combine them into one group. Notably, the NHIS did not collect data on sexual orientation until 2013, so we are unable to identify gay and lesbian respondents who are not in cohabiting relationships for a majority of the study years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation